Sieviešu un vīriešu dzimtes tēlu pozicionējums Latvijas Radio 1 jauniešu raidījumos 2005.g. - Konohovs, Artjoms (Latvijas Universitāte, 2006)
Latvijas Universitātes Sociālo zinātņu fakultātes Komunikācijas zinātnes nodaļā tapušā bakalaura darba „Sieviešu un vīriešu dzimtes tēlu atainojums Latvijas Radio 1 jauniešu raidījumos” galvenais uzdevums bija analizēt Latvijas Radio 1 jauniešu raidījumus, nozīmīgākais no kuriem ir raidījums „Radiobumba”, no dzimtes perspektīvas, ka arī noskaidrot, vai raidījuma saturs atbilst Latvijas Radio, kā sabiedriskajām medijiem, formulētajiem uzdevumiem. Pētījums ir balstīts uz Roberta Konela, Helēnas Siksū un Lūsas Iragarajas darbiem dzimtes pētniecības un feminisma studiju jomā, ka arī uz Soņas Livingstones darbiem par mediju ietekmi uz jauniešu attīstību. Analīzei ir izmantota multiparadigmālā pieeja apvienojot tādu kvalitatīvo pētniecības metodi kā sarunu analīze ar kvantitatīvo metodi – kontentanalīzi. Analīze ir atklājusi, ka abi dzimumi raidījumā „Radiobumba” tiek reprezentēti sterotipizēti vadoties pēc tradicionāliem dzimtes hierarhijas kanoniem. Savukārt žurnālistiem trūkst kritiskas attieksmes pret raidījuma saturu, kas veicina stereotipi atražošanu ēterā. Tādēļ raidījuma saturu būtu nepieciešams uzlabot, lai tas atbilstu Latvijas Radio kā sabiedriskajam medijam izvirzītajām prasībām un funkcijām, ka arī būtu interesantāks jauniešiem.

This research paper aims to analyze the quality of youth programs of Public Radio of Latvia (Latvijas Radio) both from gender research and program quality perspective. Until now there has been almost no research on public radio in Latvia, neither about youth programs of it from gender perspective. That’s why this paper aims to create a basis for both future research in this field and positive change in program quality. The paper is based on Robert W. Connell’s works on masculinity; Helene Cixous manifest “The laugh of Medusa” and her ideas of female identity and subjectivity. There has also been used some theoretical statements of Lucy Irigaray about gender and writing process. A statement about the impact of media on kids and adolescents has been based on the books written and edited by Sonia Livinigstone. As a research methodology has been chosen the qualitative method of conversational analysis and quantitative method of content analysis. The conversation analysis has been used for analyzing for interviews (2 male and to female), but the aim of content analysis was to understand the wider context of male and female representation in the analyzed programs. The results of the research has shown that both male and female are represented in stereotypic way according to traditional gender view and hierarchy where male is positioned higher than the female. The content analysis has shown the larger number of female actors than male, but conversational analysis ahs proved that female character has to face more stereotypes in the attitude of the interviewer. That’s way it reasonable to claim that simply representation of larger number of female characters can not solve gender stereotype problem. Both the characters and the program authors position stereotyped statements that are not critically analyzed or confronted. This leads to automatic producing of stereotypes at the level of utterance without deeper understanding of their true meaning. It is also clear that interviewer lacks interests to his interviewees that manifests as a boring questions and impersonal attitude. Male characters have to deal with fewer amounts of stereotypes according to the conversational analysis. But their representation is still very narrow. The dominance of hegemonic masculinity in the content can be easily seen. Representation lacks male (and also female) with different sexualities, different races and opinions. There has been only white male and female represented in the youth programs! That approves that the content of the youth programs has to be revised and the level quality of journalism has to be raised. There are also structural changes in positioning youth programs needed in order to raise the number of audience.
Positioning of the Image of Women and Men in Radio Latvia Youth Broadcasts (2005)
Keywords: Komunikācijas zinātne